2018
DOI: 10.1002/pros.23476
|View full text |Cite
|
Sign up to set email alerts
|

Effect of FAK inhibitor VS‐6063 (defactinib) on docetaxel efficacy in prostate cancer

Abstract: Our findings suggest that co-administration of the FAK inhibitor, VS-6063, with docetaxel represents a potential therapeutic strategy to overcome docetaxel resistance in prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 25 publications
0
37
0
Order By: Relevance
“…Increased phosphorylation of FAK at Y925 was observed within our prostate CAF compared with patient-matched NPF, indicating that this may represent a common microenvironmental signaling pathway across different solid tumor types (51, 54). Further, a recent study has shown that FAK is up-regulated during prostate cancer progression and promotes resistance to chemotherapy (82), supporting the use of concomitant FAK inhibitors with standard-of-care treatment. Similarly, next generation LOXL2 inhibitors are effective in pre-clinical models of gastric (83) and breast cancer (40, 84, 85) as well as lung and liver fibrosis models (86), with targeted therapeutics against LOXL2 currently undergoing Phase I/II testing (54).…”
Section: Discussionmentioning
confidence: 98%
“…Increased phosphorylation of FAK at Y925 was observed within our prostate CAF compared with patient-matched NPF, indicating that this may represent a common microenvironmental signaling pathway across different solid tumor types (51, 54). Further, a recent study has shown that FAK is up-regulated during prostate cancer progression and promotes resistance to chemotherapy (82), supporting the use of concomitant FAK inhibitors with standard-of-care treatment. Similarly, next generation LOXL2 inhibitors are effective in pre-clinical models of gastric (83) and breast cancer (40, 84, 85) as well as lung and liver fibrosis models (86), with targeted therapeutics against LOXL2 currently undergoing Phase I/II testing (54).…”
Section: Discussionmentioning
confidence: 98%
“…For example, the CD47 blocking protein TTI-621 (Petrova et al, 2017) is currently being assessed in a number of phase I clinical trials (NCT03013218, NCT02663518, NCT02216409, NCT02678338) for various types of cancers. Other groups have targeted FAK with the inhibitor VS-6063 (Defactinib) (Lin et al, 2018), which has completed clinical phase I and II trials (NCT01778803, NCT01943292, NCT01951690) with one of those clinical trials assessing for CSCs as an endpoint (NCT01778803). Other inhibitors of stemness-related molecules further downstream of ECM signaling are also being tested in clinical trials, such as the STAT3 inhibitor BBI-608 (Sonbol et al, 2019) in a phase II trial that will test for presence of CSC as an endpoint (NCT02279719) and in a phase III clinical trial aimed at reducing CSCs by targeting phosphorylated Stat3 positive cancer cells (NCT02753127).…”
Section: Csc Targeting Therapiesmentioning
confidence: 99%
“…So, the drug combination therapy can show better results in cancer treatment especially in PCa because most of the PCa patients become androgen resistant upon androgen ablation therapy . Moreover, docetaxel is the most common chemotherapeutic agent used in PCa where a combination treatment of focal adhesion kinase (FAK) inhibitor VS‐6063 with docetaxel found higher growth inhibition and increased apoptosis in PCa cell line PC3 . In another study on PCa, the combination treatment of docetaxel and curcumin repressed the cell proliferation and prompted apoptosis significantly higher than the single treatment of either docetaxel or curcumin by repressing the expression of EGFR, HER2, RTKs, PI3K, pAkt, NF‐kappa B, and COX‐2 and by increasing the expression of proapoptotic proteins P53, BAX, BAKm and BID .…”
Section: Targeting Oncogenic Deubiquitinase As the Possible Therapeuticsmentioning
confidence: 99%